Report on one serious case of ichthyophonus infection in rainbow trout - ΠΝΕΥΜΑΤΙΚΑΤΟΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author describe a case of a grave form of Ichthyophonus infection in rainbow trout observed in a unit of trout culture. According to the author, the grave effects of the disease and the serious stress in the whole population of the unit is due to the fact that the fungous infection took place during the young age of the trouts and especially during the period of the ossification of the cartilaginous tissue. The infection gave rise to a high mortality in small fishes and serious abnormalities were observed at the final formation of the bones of the vertebral column to all trouts survived after the infection.